Bilateral asynchronous sudden sensorineural hearing loss and bilateral superior semicircular canal dehiscence*. (3rd April 2018) - Ibrahim, Iman; Sweet, Robert
Abstract: Objective: To describe a case of bilateral asynchronous sudden sensorineural hearing loss (SSNHL) in a patient with bilateral superior semicircular canal dehiscence (SSCD). Study design: Case report and review of the literature. Results: A 38-year-old male, with prior SSNHL in the left ear, presented with SSNHL in the right ear. The patient had a sense of disequilibrium, but no spinning vertigo. The physical examination revealed only bilateral hearing loss at the audiometric tests and nasal polyposis. The audiogram revealed severe SNHL with fair speech discrimination on the left, and severe-to-moderately severe SNHL with good speech discrimination on the right. Distortion product otoacoustic emissions (DPOAEs) were absent. Vestibular-evoked myogenic potential (VEMP) thresholds were reduced and amplitudes elevated bilaterally. Electronystagmography (ENG) revealed bilateral hypoactive caloric responses. Blood tests were significant for elevated erythrocyte sedimentation rate, C-reactive protein, IgE, and mumps IgG titer. Gadolinium-enhanced magnetic resonance imaging was unremarkable except for sinonasal disease and a suggestion of bilateral SSCD which was confirmed by high-resolution computed tomography. Conclusion: We report a case of a bilateral SSCD associated with bilateral asynchronous SSNHL. SSCD should be considered in the differential diagnosis of SSNHL.